2018
DOI: 10.1080/10803548.2018.1443593
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health risk assessment of volatile organic compounds emitted from the coke production unit of a steel plant

Abstract: In this study, cancer and non-cancer risks of exposure to volatile organic compounds in the coke production unit of a steel plant were evaluated. To determine individual exposure to benzene, toluene, xylene and ethylbenzene, personal samples were taken from the breathing zone of workers according to National Institute for Occupational Safety and Health (NIOSH) method 1501. Cancer and non-cancer risk assessment was performed, using US Environmental Protection Agency (US EPA) methods. Samples analysis showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The possible exposure to benzene in coke oven workers has been reported in previous studies. Dehghani and co-workers determined the levels of benzene, toluene, xylene, and ethylbenzene in the breathing zone air of workers through individual sampling in the coke-making unit of a steel plant and found that benzene levels were higher than the local exposure limits [20]. In another study, toluene and benzene were among the highest VOCs present in the workplace air of the coke-making process; however, the authors evidenced that the concentrations of workplace air pollutants were lower than their local hazardous air pollutant standards for workplace air [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible exposure to benzene in coke oven workers has been reported in previous studies. Dehghani and co-workers determined the levels of benzene, toluene, xylene, and ethylbenzene in the breathing zone air of workers through individual sampling in the coke-making unit of a steel plant and found that benzene levels were higher than the local exposure limits [20]. In another study, toluene and benzene were among the highest VOCs present in the workplace air of the coke-making process; however, the authors evidenced that the concentrations of workplace air pollutants were lower than their local hazardous air pollutant standards for workplace air [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, coke oven workers might also be exposed to VOCs emitted during destructive distillation. Indeed, a certain number of studies assessed the exposure to VOCs in coke oven workers quantifying their levels in workplace and breathing zone air, with overall levels ranging from 22.6 µg/m 3 to 2.17 mg/m 3 [20][21][22][23][24][25][26][27][28]. Only a few studies performed biomonitoring of VOC metabolites in coke oven workers.…”
Section: Introductionmentioning
confidence: 99%
“…[36], supported this by stating that damages caused to houses by external forces include damages to doors, windows, roofs and other parts of building due to strong winds and erosion that threatens building foundation which are mostly triggered by illicit digging of boreholes and water wells in residential areas. [37] also stated that poor waste disposal near houses and homes makes occupants prone to diseases and rodents attacks. Similarly, the results presented in Table 3 reveals the possible ways of mitigating the threats posed by the environmental factors on buildings.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…However, this method’s most important limitation is that it cannot consider the synergistic effects of hybrid solutions. 22 …”
Section: P Articipants and M Ethodsmentioning
confidence: 99%